2015
DOI: 10.1007/s13224-015-0760-3
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Case–Control Study Evaluating the Role of Mifepristone for Induction of Labor in Women with Previous Cesarean Section

Abstract: Objective To investigate the role of ''mifepristone'' for induction of labor (IOL) in pregnant women with prior cesarean section (CS).Methods In this retrospective study, all pregnant women with prior CS who received oral mifepristone (400 mg) for IOL (as per clear obstetric indications) [group 1] were compared with pregnant women with prior CS who had spontaneous onset of labor (SOL) [group 2], with respect to incidence of vaginal delivery, CS, duration of labor, and various maternal and fetal outcomes. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…There were no differences in main neonatal outcomes in our study. The same results were found in other studies [26,27,29]. Bercane and coworkers (2005) did not find any signs of peripheral cortisol deprivation in the neonates despite the mifepristone concentration ratio between umbilical cord blood and maternal blood was 1:3 [16].…”
Section: Commentsupporting
confidence: 87%
See 1 more Smart Citation
“…There were no differences in main neonatal outcomes in our study. The same results were found in other studies [26,27,29]. Bercane and coworkers (2005) did not find any signs of peripheral cortisol deprivation in the neonates despite the mifepristone concentration ratio between umbilical cord blood and maternal blood was 1:3 [16].…”
Section: Commentsupporting
confidence: 87%
“…More recent studies showed improvement in cervical score within 24-48 h, decline the cesarean rate, amount of dose requirement of augmentation of labour, lesser NICU admission and maternal complication after mifepristone induction in term and prolonged pregnancy [25,26]. There is report of the use of mifepristone for induction of labour in women with previous cesarean section [27].…”
Section: Introductionmentioning
confidence: 99%
“…7 There is report of the use of Mifepristone for induction of labour in women with previous cesarean section. 8 Therefore, it is still of interest to continue studies, which will help to evaluate efficacy and safety of mifepristone for labor induction in full-term pregnancy.…”
Section: 5mentioning
confidence: 99%